Ranking of factors affecting environmental pollution - Li, Chang (International journal of industrial engineering and operational research, 2023)
This paper aims to analyze and rank the factors that significantly contribute to environmental pollution. Environmental pollution poses severe threats to ecosystems, human health, and overall sustainability. By understanding the key factors involved, effective mitigation strategies and policy interventions can be implemented. This study employs a comprehensive literature review, quantitative analysis, and data interpretation to ascertain the relative importance of various factors contributing to environmental pollution. The findings of this research can guide policymakers, environmentalists, and stakeholders in making informed decisions to protect and conserve the environment.